Nachbarsprache & buurcultuur: Results of the academic critical monitoring of a school exchange project in the German-Dutch border region - Jentges, Sabine; Sars, Paul (Glottodidactica, 2022)
In the years 2017–2021, the school exchange project Nachbarsprache & buurcultuur was carried out in the German-Dutch border region and funded by the EU as an Interreg Va-project. During the entire project period, the exchanges that took place were critically monitored. In this article, we (as project managers from the Dutch side) go into the available scientific findings and basic requirements for ‘successful’ encounters in school exchanges, as well as selected critical results from the monitoring of the project Nachbarsprache & buurcultuur for the areas of pluricultural or culture-reflective and multilingual learning in exchanges.